2011
DOI: 10.1186/1471-2407-11-71
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant methylation of Polo-like kinase CpG islands in Plk4 heterozygous mice

Abstract: BackgroundHepatocellular carcinoma (HCC), one of the most common cancers world-wide occurs twice as often in men compared to women. Predisposing conditions such as alcoholism, chronic viral hepatitis, aflatoxin B1 ingestion, and cirrhosis all contribute to the development of HCC.MethodsWe used a combination of methylation specific PCR and bisulfite sequencing, qReal-Time PCR (qPCR), and Western blot analysis to examine epigenetic changes for the Polo-like kinases (Plks) during the development of hepatocellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…A previous study showed that both mRNA and protein expressions of PLK4 gradually decreased from normal liver to HCC [24]. In this study, to elucidate the clinical role of PLK4 in HCC, we applied TMA and IHC to examine its expression in a cohort of Chinese patients.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that both mRNA and protein expressions of PLK4 gradually decreased from normal liver to HCC [24]. In this study, to elucidate the clinical role of PLK4 in HCC, we applied TMA and IHC to examine its expression in a cohort of Chinese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Deregulation of PLK1 expression has also been associated with hypomethylation at the promoter region of PLK1 gene. Hypomethylation of PLK1 promoter has been observed in mouse hepatocellular carcinoma53 54 and human haematological malignancies 55. The loss of methylation correlated (75.7% in haematological malignancies) with elevated PLK1 expression in tumour cells.…”
Section: Plk1 and Oncogenesismentioning
confidence: 96%
“…PLK4 acts as a tumor suppressor in hepatocellular carcinoma (HCC). 100 PLK4 production is reduced during hepatic carcinogenesis by promoter hypermethylation 101 and might contribute to HCC development in infertile men who carry a mutation in PLK4. 98,102 103 It regulates homologous chromosome synapsis and double-strand DNA breakage repair.…”
Section: Plk4 and Sertoli-cell-only Syndromementioning
confidence: 99%